122 ISAKOS subclassification of Rockwood type III AC joint dislocations in a stable and an unstable type is not clinically relevant. (25th January 2023) - Haugaard, Kristine; Bak, Klaus; Ryberg, Dorthe; Muharemovic, Omar; Hölmich, Per; Barfod, Kristoffer Weisskirchner
Abstract : Background: ISAKOS upper extremity committee has suggested a subclassification of Rockwood type III acromioclavicular(AC) joint dislocations in a stable type A recommended non-surgical treatment and an unstable type B recommended surgical treatment. The objective of this prospective cohort study was to investigate if this subclassification is clinically relevant. Methods: Inclusion criteria were patients aged 18–60 with acute AC joint dislocation and >50% superior displacement of the clavicle. Patients were treated non-surgically with 3m of home-based training and the option of delayed surgical intervention. Assessment was at baseline and 6w, 3m, 6m and 1y after the injury. At 6w, patients were classified as stable if they presented with no scapular dyskinesis (SD) and no overriding of the clavicle to the acromion on radiographs, and unstable if they presented with any of the two. The primary outcome was the Western Ontario Shoulder Instability Index(WOSI). Results: Eighty-eight patients contributed data for the subclassificaton at 6w; 20 patients were classified as stable and 68 as unstable. There was a statistically significant but not clinically relevant difference in WOSI between the two groups at 6m (p=0.03), but not at 3m and 1y. No patients from the stable group had surgery. From the unstable group, 9/68 (13%) had surgery. Patients presenting with SD had worse WOSI at all time-points compared to those without SD. Conclusion: The ISAKOS subclassification of Rockwood type III in a stable type A and an unstable type B is not clinically applicable. The presence of SD was associated with a worse result.